Skatinimo raiškos konkurencija lietuvių kalboje - Župerka, Kazimieras (Kalbotyra, 1990)
The aspect of competition of means of a language determines the way of research from communicative intention to expression. Expression of exhortation in Lithuanian distinguishes itself with abundance of competing means. The main construction is hortatory sentence with the 2nd person of imperative mood; transposed constructions of interrogative and declarative sentences have the intention of exhortation, transposed forms of subjunctive and indicative mood, infinitive, 3rd person and pluralist person make a turn of competing grammatical forms; competing constructions of personal and impersonal, complex and simple (condensed) sentences can express exhortation. It is necessary to inventory competing means of standard speech acts; it is purposive to take sentence-utterance as the unit of competitors inventory.